RNA-mediated specificity of DNA packaging into hybrid lambda/phi 29 proheads. - Valpuesta, J M (1993)
A small RNA (pRNA, 174 nt) is known to be essential for DNA packaging in bacteriophage phi 29. However, in an in vitro DNA packaging system based on hybrid lambda/phi 29 proheads (made up of head proteins from phage lambda and connectors from phage phi 29), the specificity of DNA packaging is lost, and different RNA molecules fulfil the requirements for DNA packaging, albeit with less efficiency than phi 29 pRNA. Competition assays with RNAs from different sources have shown that phi 29 connectors bind preferentially pRNA. An increase in the efficiency of phi 29 DNA packaging into hybrid proheads induced by phi 29 pRNA is observed because, when phi 29 pRNA is incubated with hybrid proheads, phi 29 DNA is packaged more efficiently than other DNAs of similar length. Furthermore, when hybrid proheads carrying phi 29 pRNA are incubated with a mixture of DNAs from different sources, phi 29 DNA is selectively packaged, thus indicating that phi 29 pRNA determines the specificity of DNA packaging.